MODIFIED SURGICAL TECHNIQUES FOR RESECTION OF PARAGANGLIOMAS OF THE CAROTID BIFURCATION - A. Z. Almyashev (Опухоли головы и шеи)
The paper presents the current principles of surgical treatment for carotid paragangliomas and the prevention of intraoperative neurovascular complications.